2022
DOI: 10.1155/2022/4273691
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect and Threshold Effect of Green Finance on Carbon Intensity: From the Perspective of Capital Accumulation

Abstract: Climate change has caused serious threats to global economic development and human well-being, and green finance is a new way to achieve ecological, economic, and social sustainable development, and it also has important theoretical significance and policy value. This study firstly aims to study the impact of green finance on regional carbon intensity. Then, it aims to determine the moderating effect of capital stock per capita on the relationship between green finance and carbon intensity based on moderating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…China is a policy development-oriented country, and the state and its policies occupy an extremely important position at the level of environmental governance. Generally speaking, the more funds are invested in environmental management, the greater the supervision on the environment [47]. The percentage of investment in reducing environmental pollution to GDP is used to represent it.…”
Section: Control Variablesmentioning
confidence: 99%
“…China is a policy development-oriented country, and the state and its policies occupy an extremely important position at the level of environmental governance. Generally speaking, the more funds are invested in environmental management, the greater the supervision on the environment [47]. The percentage of investment in reducing environmental pollution to GDP is used to represent it.…”
Section: Control Variablesmentioning
confidence: 99%
“…Kapa et al [13] investigated six countries that account for 61% of global carbon emissions and discovered that green finance contributes to a remarkable reduction in carbon intensity. Zhang and Ke [14] found that every 1% increase in green finance development results in a 2% decrease in carbon intensity. Du [15] confirmed that both short and longterm estimates of green finance significantly reduce carbon intensity using the quantile autoregressive distributed lag (QARDL) model.…”
Section: Green Finance and Carbon Intensitymentioning
confidence: 99%
“…In terms of the relationship between green finance and SDRE, some scholars believe that the threshold mechanism of green finance is conducive to narrowing the regional gap of sustainable development. Nevertheless, the inhibition effect of green finance on carbon intensity is affected by the structure of factors in different regions [16,17]. Zhou et al (2022) [18] studied the impact of green finance on regional ecological development in China, and they found boundary differences among the eastern, central, and western regions.…”
Section: Introductionmentioning
confidence: 99%